Investigation of traffic noise pollution at puchong residential areas - Nazri N.N.I.M.; Mardi N.H.; Zaini N.; Norhisham S.; Naim N.N.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Acoustic noise; Housing; Offshore oil well production; Surveys; Water pollution; Environmental pollutions; Health effects; Previous year; Residential areas; Source of noise; Time interval; Traffic noise; Traffic volumes; Noise pollution